Semiotic Analysis of Roland Barthes on Wardah Advertisement Version “I Face of Indonesia” - Nurhasanah Purba; Khairunnisa Tambunan (LingLit Journal Scientific Journal for Linguistics and Literature, 2021)
This study aims to represent the meaning of the advertisement using Barthes' semiotic sign map and to describe the meaning contained in the wardah advertisement version of "I am the face of Indonesia". This study uses qualitative methods to describe the object of research in accordance with what was observed and captured from the data obtained. In addition, the purpose of this method is to assist the research process by providing a more accurate picture. The results of this study indicate that the version of Wardah advertisement "I am the face of Indonesia is an advertisement that has motivation and solutions to the problems faced by many women in Indonesia, namely certain insecure (lack of confidence) in its delivery to Indonesian women who are potential consumers of the wardah version" I face Indonesia ”. This advertisement has two interrelated and complementary meanings, namely denotation meaning and connotative meaning. In advertisements, there are choices of signs to represent a phenomenon that is raised until it is interpreted by the public and up to the formation of discourse on the advertisement.